2019
DOI: 10.1108/edi-02-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

School context: implications for teachers of color

Abstract: Purpose By 2026, students of color will make up 54 percent of the school-age population. Literature on recruiting and retaining teachers of color reveal that teachers of color are underrepresented in US schools (Castro et al., 2018). Cultural differences between teachers and students result in higher number of students of color being expelled or suspended, low graduation rates and lower numbers of students of color in advanced math, science and gifted courses. With an emphasis on retaining teachers of color th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…With the heightened awareness surrounding racism and acts of violence in today’s society, it is important for educators to not only understand marginalized youth but also the challenges that all people of color face. All too often, teachers of color are expected to be the experts and communicate with all “African American parents, provide insight on areas of discipline strategies and be responsible for administering the multicultural events” (Madsen et al, 2019, p. 68). Therefore, educators need the support of school and district leaders paired with professional development focused on creating equitable learning environments.…”
Section: Climate and Culturementioning
confidence: 99%
“…With the heightened awareness surrounding racism and acts of violence in today’s society, it is important for educators to not only understand marginalized youth but also the challenges that all people of color face. All too often, teachers of color are expected to be the experts and communicate with all “African American parents, provide insight on areas of discipline strategies and be responsible for administering the multicultural events” (Madsen et al, 2019, p. 68). Therefore, educators need the support of school and district leaders paired with professional development focused on creating equitable learning environments.…”
Section: Climate and Culturementioning
confidence: 99%
“…Another study by Evans (2007a; 2007b) noted similar concerns where these schools adopted a colorblind belief, which led to minimization of African Americans’ cultural values and did not change the deficit thinking framework. Madsen et al (2019) revealed additional concerns about the challenges teachers of color face in schools with changing demographics (Madsen & Mabokela, 2005).…”
Section: Student Voice and School Changementioning
confidence: 99%
“…In most cases, a school inclusion model requires schools to refocus their practices to be more accommodating to today's students. In schools undergoing a dramatic shift in their student demographics, it requires a concerted effort where administrators need to make the necessary changes to ensure students feel connected (Torres et al, 2018; Madsen et al, 2019).…”
Section: Student Voice and Changing School Demographicsmentioning
confidence: 99%
“…Revista Electrónica Educare (Educare Electronic Journal) EISSN: 1409-4258 Vol. 27(1) ENERO-ABRIL, 2023: 1-24 Los artículos sobre 'características de las escuelas' discuten formas alternativas de configurar las escuelas (Viçosa y Menezes, 2015;Shay y Heck, 2015;Macdonald et al, 2018), su infraestructura (Moss et al, 2017), ambiente laboral (Wright y Smith, 2015;Madsen et al, 2019), u otras que afectan el proceso educativo o cómo impactan a sus actores (Gómez Fernández y Siry, 2018; Gorete Neto, 2014).…”
Section: Objetivos Y Enfoques De Los Estudiosunclassified